Incidence of and Risk Factors for Paradoxical Psoriasis or Psoriasiform Lesions in Inflammatory Bowel Disease Patients Receiving Anti-TNF Therapy: Systematic Review With Meta-Analysis - Xie, Wenhui; Xiao, Shiyu; Huang, Hong; Zhang, Zhuoli (Frontiers in Immunology, 2022)
Background: Paradoxical psoriasis or psoriasiform lesion induced by anti-tumor necrosis factor (anti-TNF) therapies received increasing attention worldwide. However, no comprehensive meta-analysis investigating the incidence estimates and risk factors for anti-TNF-induced psoriasis is currently available. We aimed to precisely quantify its incidence as well as risk factors in patients with inflammatory bowel disease (IBD). Methods: This study was registered on PROSPERO database under review registration number CRD42021233695. Electronic databases PubMed, EMBASE and the Cochrane library were comprehensively searched. Observational studies published as full-length papers in English and reporting the incidence and/or predictors for psoriasis or psoriasiform lesions in IBD patients. A random-effects meta-analysis was performed to calculate pooled incidence. Pooled odds ratio (OR) and 95% confidence interval for potential predictors were combined using fixed-effects or random-effects model. Results: In total, 30 articles comprising 24,547 IBD patients treated by anti-TNF were finally included. The overall pooled incidence of psoriasis and/or psoriasiform lesions following anti-TNF therapy was 6.0% (5.0%-7.0%; I2=93.9%), with 6.9% (5.1%-8.7%; I2=92.4%) for psoriasiform lesions and 4.6% (3.6%-5.6%; I2=93.9%) for psoriasis. Multivariable meta-regression indicated regions and populations significantly contributed to the heterogeneity. Statistically higher risk for psoriasis or psoriasiform lesions during anti-TNF therapy was observed in female (OR 1.46, 1.23-1.73), younger age at anti-TNF initiation (OR 1.03, 1.00-1.05), smoking (OR 1.97, 1.56-2.48) ileocolonic Crohn's disease (OR 1.48, 1.03-2.13) and adalimumab or certolizumab usage (vs. infliximab) (OR 1.48, 2.87 respectively). Conclusions: The incidence of psoriasis or psoriasiform lesions was not uncommon in IBD patients following anti-TNF therapy. Female, younger age, smoking, ileocolonic Crohn's disease and the types of anti-TNF were significantly associated with such risk. These findings may help gastroenterologist to make more individualized decisions and understand the mechanisms of this paradoxical phenomenon.